Tetracycline-inducible transfer of tetracycline resistance in Bacteroides fragilis in the absence of detectable plasmid DNA. - Rashtchian, A (1982)
Tetracycline resistance of three Bacteroides fragilis strains was shown to be inducible by subinhibitory concentrations of tetracycline. Tetracycline resistance markers could be transferred to another B. fragilis strain by filter mating. The transferability was inducible by subinhibitory concentrations of tetracycline and did not take place in the absence of tetracycline. The optimum concentration of tetracycline for induction of transfer was about 2 microgram/ml. The transfer was shown to be a conjugation-like process requiring cell-to-cell contact between donor and recipient. Screening of parental donor strains for the presence of plasmid DNA did not demonstrate any detectable plasmids in two of the strains. A 3.0-megadalton plasmid, designated pBY5, was present in the third donor strain. Mobilization of pBY5 by another plasmid (pBF4) showed that pBY5 did not carry the genes responsible for tetracycline resistance. It appears that the genes responsible for resistance to tetracycline as well as those responsible for conjugal transfer may be carried on the chromosome in all three donor strains.